Penerapan Metode Linier Dalam Menghitung Keuntungan Maksimum Kopi Susu Di KOGNITIF.CO - Mario, Riko; Saputro, Niko; Rahman, Wildan Abdul (STMIK TIME, 2019)
Linear Programming was first discovered by a US statistician named Prof. George Dantzig (Father of the Linear Programming). Linear programming is a mathematical technique that is designed to assist managers in planning and making decisions in allocating limited resources to achieve company goals. The company's goal in general is to maximize profits, but due to limited resources, the company can also minimize costs. Problem solving leads to the achievement of the objectives of maximization or minimization. The existing constraints limit the level of achievement of goals. Has several settlement alternatives. Mathematical relationships are linear. To calculate the benefits of selling milk coffee in the current cognitive.co business. As for achieving these goals, the authors use linear programming methods in the process of calculating maximum profits. Supporting software tools used are POM for windows. Calculation of maximum profits is expected to simplify and speed up the calculation process.